2023
DOI: 10.1007/s40122-023-00483-4
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam Compared to Propofol During Hysteroscopy: A Safety and Efficacy Analysis

Abstract: Introduction Propofol is the main drug used to induce sedation for endoscopic procedures, and few drugs had shaken its dominant clinical use for a decade until the development of remimazolam. Remimazolam has been demonstrated to perform well in post-marketing studies on sedation for colonoscopy or other procedures requiring short periods of sedation. This study aimed to establish whether remimazolam was effective and safe for inducing sedation for hysteroscopy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several recent randomized controlled trials have compared remimazolam to propofol in procedural sedation such as gastric endoscopy and hysteroscopy. These studies have consistently demonstrated that the incidence of adverse events was significantly lower in patients administered remimazolam compared to propofol [ 29 31 ]. The time to loss of consciousness in the remimazolam group was longer compared to the propofol group [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent randomized controlled trials have compared remimazolam to propofol in procedural sedation such as gastric endoscopy and hysteroscopy. These studies have consistently demonstrated that the incidence of adverse events was significantly lower in patients administered remimazolam compared to propofol [ 29 31 ]. The time to loss of consciousness in the remimazolam group was longer compared to the propofol group [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 However, it is undeniable that propofol has time- and dose-dependent depressive effects on the cardiovascular and respiratory systems, which limits its use in basic hospitals with a shortage of anesthesiologists and subpar resuscitation facilities. In conjunction with propofol, opioids (such as fentanyl, 16 sufentanil, 5 and remifentanil 3 ) are frequently used for general intravenous anesthetic during day-case surgery for hysteroscopy. Because PK and/or PD interactions may alter medication dose–effect relationships, they are often not explored separately when thinking about therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous injections included sufentanil at 1 ug/kg and granisetron at a 0.3 mg. The sedation regimens were propofol (Yangtze River Pharmaceutical Co., Ltd) at 1.5 mg/kg (P), remimazolam (Yichang Renfu Pharmaceutical Co., Ltd) at 0.3 mg/kg (R1) [6], and remimazolam at 0.2 mg/kg (R2) [7], with regiment allocation randomized using sealed envelopes. The operation began when the Narcotrend index (NI) was ≤ 64 or the Modi ed Observer's Assessment of Alertness/Sedation Scale (MOAA/S) was ≤ 2.…”
Section: Study Methodsmentioning
confidence: 99%
“…Propofol is preferred for its rapid onset, quick recovery, and effective sedation, but it may induce respiratory and circulatory inhibition. Alternatively, remimazolam, an ester-based benzodiazepine, offers rapid onset, high clearance [2], minimal effect on hepatic or renal function [3,4], and mild respiratory and circulatory inhibition [5][6][7], It is effective in inducing sedation during bronchoscopy [5,8,9], ERCP [6], and hysteroscopy [7]. This study aimed to evaluate the clinical e cacy and safety of sedation using both propofol and remimazolam in the same patient with cervical cancer undergoing three sessions of interstitial brachytherapy.…”
Section: Introductionmentioning
confidence: 99%